Green science: Decoding dark photon structure to produce clean energy. (November 2018) - Hossain, Md. Faruque
Abstract: To produce energy from dark photon γ ̄, I have proposed it to collide with Higgs-boson BR(H → γ γ ̄ ) quantum under extreme relativistic condition ( ERC ). Just because Higgs-boson, BR(H → γ γ ̄ ) quantum get excited at extreme relativistic condition and its quantum field get extreme short-range week force to create electromagnetic field. Thus, I have assumed that the results of electrically charged particles of dark photon γ ̄ (non-energy level photon) into the extreme relativistic condition shall indeed create energy level photon, here named as Hossain Dark Photon ( HdP − ). To confirm this HdP − transformation by Higgs boson BR(H → γ γ ̄ ) quantum interaction, I have performed series of mathematical modeling by using MATLAB software. Interestingly, the mathematical calculation revealed that the presence of an extra relativistic condition does transform dark photon γ ̄ into HdP − at N e f f = 4 . 0 8 − 0 . 68 + 0 . 71 at 95% level l.c. (confidence limit) respectively dark photon's speed c eff and viscosity c vis parameters as d c e f f = 2 0 . 312 ± 0 . 026 and c v i s 2 = − 0 . 16 + 0 . 21, consistent with the expectations of a relativistic free streaming component c e f f = 2 c v i s 2 = 1 ∕ 3 . With the presence of N e f f, the HdP − photon transformation dynamics was also modeled at nano scale by cavity waveguides circuit considering atomic spectra contour maps of Hamiltonian ( H = ∑ ω c i a i † a i + ∑ K ω k b k † b k + ∑ i k V i k a † b k + V i k ∗ b k † a i ) embedded in a semiconductor. The result revealed that the transformation of Hossain Dark Photons ( HdP − ) by Higgs-boson [BR(H → γ γ ̄ ] particle reaction under extreme relativistic condition ( ERC ) are very much energy level to produce the electricity.